Economic experiments in designing new agricultural policies and measures - Dragi Dimitrievski; Marina Nacka; Riste Elenov; Ivana Janeska Stamenkovska; Efimija Dimovska (ARPHA Proceedings)
The agricultural sector in North Macedonia continues to face structural and productivity challenges, compounded by weak market integration and a lack of innovative policy responses. Economic experiments provide a structured framework for understanding behavioral responses to policy interventions, facilitating the development of more effective agricultural policies. This study examines the effectiveness of different policy measures in encouraging youth engagement in farming. A pilot survey was conducted with 77 agricultural university students to assess their responses to three distinct policy scenarios: (1) financial support for business investments, (2) allocation of state-owned land, and (3) a combined land-and-housing incentive. The findings indicate that financial support and structured investment mechanisms are more effective in encouraging agricultural participation than land-based incentives alone. While the student sample was selected for its familiarity with agricultural issues and potential future involvement in the sector, the results may not fully reflect the decision-making behavior of active young farmers. These insights contribute to evidence-based policymaking by offering empirical guidance for designing agricultural policies that better support youth participation in the sector.